FUNCTIONAL ASSESSMENT OF MOTOR FUNCTION IN CHILDREN WITH SPASTIC HEMIPARETIC CEREBRAL PALSY (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of a comprehensive functional assessment of children aged 6–12 years with cerebral palsy (CP) in the form of spastic hemiparesis, conducted at the preparatory stage prior to physical therapy to design an individually tailored rehabilitation program. Determining the baseline level of motor impairment is a key prerequisite for developing an effective rehabilitation strategy, as a detailed analysis of the structure of motor limitations enables the formulation of specific goals, priorities, and therapeutic means according to each child’s functional potential.To objectify the degree of gross and manual motor impairments, standardized classification systems GMFCS (Gross Motor Function Classification System) and MACS (Manual Ability Classification System) were employed, providing an integrated assessment of activity level and participation in motor tasks. To quantify manual dexterity, the Box and Block Test was used to determine the degree of motor asymmetry between the paretic and non-paretic upper limbs.Analysis of the obtained data made it possible to characterize the typical structure of impairments among children classified within levels I–III on the GMFCS and MACS scales, and to identify relationships between the severity of manual dysfunction, reduced motor dexterity, and increased asymmetry. No statistically significant differences were found between the main and control groups, confirming their homogeneity at the pre-intervention stage.The findings emphasize the diagnostic, prognostic, and practical significance of an in-depth functional assessment that combines classification-based and quantitative methods. This approach provides a scientifically grounded basis for personalized planning of physical therapy programs aimed at targeted restoration of motor functions and improvement of quality of life in children with cerebral palsy.
Keywords: cerebral palsy; spastic hemiparesis; GMFCS; MACS; Box and Block; functional assessment; physical therapy; rehabilitation planning